A escola como espaço de formação continuada de professores: o caso da Escola Cidade de Emaús, Belém/Pa - BARROS, Maricilda Nazaré Raposo de (2004)
In this research, I have perspective, contribute for the discussion of the continued formation of teachers centered in school, having as locus of research the School City of Emaús, in Belém/Pa. With the purpose to knowing the process of continued formation taken place in this school it analyzes primary documents of the Institution, that deal with its philosophy, of the social statute of the maintainer entity, of the politician-pedagogical project, among others and interviews with 06 diligent teachers of this experience who had started to participate of the school space in elapsing of the considered period, in which if it includes author and its proper memories. For the reconstitution of the process I used the narrative research, looking for evidence the implanted partner-pedagogical experience since the decade of 1980 that it is configured since than, as one other/new proposal educational up to 2003. Considering for the study of the process the following axles of analysis: the formative organization of space and pertaining to school time and actions in the school, considering there the collective work, the production of didactic materials, the politic social involvement and the activities done in the district. I discuss the advances and limitation of the continued formation of teachers centering in the school and I search to point out ways to the construction of the necessary teacher to proposal of a politician-pedagogical project to this educative space, it still looks, to join technique ability to the commitment politician. This formation must assure the permanent confirmation and evaluation of the philosophy assumed by the school, as well as all theoretician-scientific recital of the work developed there, materialize the actions from the proper experience of a collective work. This formation therefore, acquires an essential character of the pertaining to school community. I also think, that from an interior politicianpedagogical project, in fact, for the diverse segments of a pertaining to school institution there are greater conditions, so that if it constructs a central axle to the continued formation of teachers, who are just integrant part of people who must concur for the same purpose. I believe the school that possess a politician-pedagogical project, compels it to the necessity of forming responsible human resources for its development.